ICT and resilience in times of crisis: Evidence from cross-country micro moments data - Irene Bertschek; Michael Polder; Patrick Schulte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
ICT-intensive firms are often found to have a better performance than their non-ICTintensive counterparts. Along with investing in ICT capital they have to adapt their production and business processes in order to reap the potentials implied by the use of ICT. Are these firms also more resilient in times of crisis? We study this question by exploiting a novel and unique data set from the Microments Database. Covering 12 countries, 7 industries and the period from 2001 to 2010, the data allow us to distinguish between ICT-intensive and non-ICT-intensive firms within industries. We find evidence that indeed during the crisis in 2008 and 2009, ICT-intensive firms were hit less hard with respect to their productivity. This holds in particular for firms from service industries. Moreover, ICT-intensive firms were also more successful in introducing process innovations during that period which could explain their better productivity performance compared to non-ICT intensive firms.
urn:nbn:de:bsz:180-madoc-434741
Keywords: H12; J24; O31; O47; 330; ICT; innovation; productivity; economic crisis; resilience; meso-level data